Pengaruh Supervisi Kepala Sekolah dan Kompetensi Pedagogik Guru terhadap Kinerja Guru di SMAN 1 Kisam Tinggi - Septiyana, Etika (Yayasan Sembilan Pemuda Indonesia, 2022)
The purpose of this study was to determine the effect of principal supervision and teacher pedagogic competence on teacher performance at SMAN 1 Kisam Tinggi. The type of research used is descriptive analysis with a quantitative approach to see the effect of the principal's supervision variable and the teacher's pedagogic competence variable on the teacher's performance variable through hypothesis testing. This study uses a questionnaire that is relevant to all variables as a data collection tool. The questionnaire used is 5 Likert scale, and has been tested for validity and reliability test. The sample in this study were all 30 teachers at SMAN 1 Kisam Tinggi. This research uses simple regression data analysis method and multiple regression. The results showed that the principal's supervision partially affected the performance of teachers at SMAN 1 Kisam Tinggi. The teacher's pedagogic competence partially influences the performance of teachers at SMAN 1 Kisam Tinggi. Principal supervision and teacher pedagogic competence simultaneously affect teacher performance at SMAN 1 Kisam Tinggi. Based on the value of the coefficient of determination test results, 82.2% of teacher performance can be explained by the supervision of the principal and pedagogic competence, meaning that there is a contribution of 82.2% given the supervision of the principal and pedagogical competence on teacher performance, and the remaining 17.8% (100%-82.2%) of the teacher's performance can be explained by other reasons.